Magnetic Nanomaterials and Nanostructures in Sample Preparation Prior to Liquid Chromatography - Georgios Antoniou; Victoria Samanidou (Magnetochemistry, 2022)
Magnetic nanomaterials and nanostructures compose an innovative subject in sample preparation. Most of them are designed according to the properties of the target analytes on each occasion. The unique characteristics of nanomaterials enhance the proficiency at extracting and enriching due to their selective adsorption ability as well as easy separation and surface modification. Their remarkable properties, such as superparamagnetism, biocompatibility and selectivity have established magnetic materials as very reliable options in sample preparation approaches. In order to comprehend the range of utilization at magnetic materials and nanostructures, this review aims to present the most notable examples in sample preparation prior to liquid chromatography (LC) to the community of analytical chemists. Primarily, the review describes the principles of the techniques in which the magnetic materials are utilized and leaned on. Additionally, there is a diligent report about the novel magnetic techniques and finally a comparison to demonstrate the total point of view.